Nanozyme-strip based on MnO2 nanosheets as a catalytic label for multi-scale detection of aflatoxin B1 with an ultrabroad working range. (30th May 2022) - Cai, Xinfa; Liang, Meijuan; Ma, Fei; Zhang, Zhaowei; Tang, Xiaoqian; Jiang, Jun; Guo, Can; Ramzy Mohamed, Sherif; Abdel Goda, Amira; Dawood, Dawood H.; Yu, Li; Li, Peiwu
Graphical abstract: Highlights: A novel nanozyme-based LFIA was fabricated for AFB1 screening. MnO2 nanosheets (MnO2 NSs) behave as both oxidase mimics and nanolabels for LFIA. MnO2 NSs-TMB chromogenic system was applied to the LFIA for the first time. The LFIA simultaneously exhibits high sensitivity and an ultrawide linear range. The LFIA offers seven detection ranges to meet the different testing needs of different allowable limits. Abstract: Lateral flow immunoassay (LFIA) is the most effective real-time detection method for aflatoxin B1 (AFB1 ). Here, we constructed a nanozyme-strip based on MnO2 nanosheets (MnO2 NSs) as a catalytic label for detection of AFB1 . By taking advantage of the MnO2 -TMB catalytic amplified system, the new test achieves rapid detection with high sensitivity and ultrawide range. The limit of detection of the assay was 15 pg mL −1, which was over 100-fold lower than the maximum limit set by the European Union (EU) of AFB1 in foods. In addition, the strip test could offer 7 dynamic detection ranges, spanning 4 orders of magnitude, which could cater to the varieties of limits on AFB1 residues in foods and feeds set by different countries. The estimated recoveries were in the range of 85.67%-106.38% with coefficients of variations (CVs) less than 9.68%. Overall, the developed approach is a rapid, reliable, sensitive and widely available tool for on-site detection of AFB1 .